SARS-CoV-2 in Exhaled Aerosol Particles from COVID-19 Cases and Its Association to Household Transmission. (10th March 2022) - Alsved, Malin; Nygren, David; Thuresson, Sara; Medstrand, Patrik; Fraenkel, Carl Johan; Löndahl, Jakob
Abstract: Background: Coronavirus disease 2019 (COVID-19) transmission via exhaled aerosol particles has been considered an important route for the spread of infection, especially during super-spreading events involving loud talking or singing. However, no study has previously linked measurements of viral aerosol emissions to transmission rates. Methods: During February–March 2021, COVID-19 cases that were close to symptom onset were visited with a mobile laboratory for collection of exhaled aerosol particles during breathing, talking, and singing, respectively, and of nasopharyngeal and saliva samples. Aerosol samples were collected using a BioSpot-VIVAS and a NIOSH bc-251 2-stage cyclone, and all samples were analyzed by RT-qPCR for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA detection. We compared transmission rates between households with aerosol-positive and aerosol-negative index cases. Results: SARS-CoV-2 RNA was detected in at least 1 aerosol sample from 19 of 38 (50%) included cases. The odds ratio (OR) of finding positive aerosol samples decreased with each day from symptom onset (OR 0.55, 95 confidence interval [CI] .30–1.0, P  = .049). The highest number of positive aerosol samples were from singing, 16 (42%), followed by talking, 11 (30%), and the least from breathing, 3 (8%). Index cases were identified for 13 households with 31 exposed contacts. Higher transmission rates were observed in households with aerosol-positive index cases, 10/16 infected (63%), compared to households with aerosol-negative index cases, 4/15 infected (27%) (χ 2 test, P  = .045). Conclusions: COVID-19 cases were more likely to exhale SARS-CoV-2-containing aerosol particles close to symptom onset and during singing or talking as compared to breathing. This study supports that individuals with SARS-CoV-2 in exhaled aerosols are more likely to transmit COVID-19. Abstract : Transmission of covid-19 via exhaled aerosol particles were identified from case reports where air samples were missing. Our study quantifies SARS-CoV-2 RNA in exhaled air and provides a direct link between positive air samples and increased household transmission.